"La forma quanto l'essere". Un'estetica alla base della diversità biologica (Itinera, 2025)
"Form as much as being". An aesthetic at the basis of biological diversityThis paper proposes an aesthetic hypothesis on biological diversity and differentiation, drawing on a joint reading of Catherine Malabou’s epigenesis of rationality and Alessandro Sarti, Giovanna Citti, and David Piotrowski’s differential heterogenesis. Despite their theoretical distance, both these perspectives investigate the emergence of novel biological forms and new underlying morphologies. We argue that both implicitly point toward an aisthesis of the living, wherein difference and differentiation precede the functional determination of morphogenetic processes.
Keywords: Form; Morphogenesis; Morphology; Plasticity